A comparison of the most intense periods (MIPs) during competitive matches and training over an 8-week period in a male elite field hockey team - Büchel, D.; Döring, M.; Baumeister, J. (Journal of Science in Sport and Exercise, 2025)
Purpose Wearables serve to quantify the on-court activity in intermittent sports such as field hockey (FH). Based on objective data, benchmarks can be determined to tailor training intensity and volume. Next to average and accumulated values, the most intense periods (MIPs) during competitive FH matches are of special interest, since these quantify the peak intensities players experience throughout the intermittent matches. The aim of this study was to retrospectively compare peak intensities between training and competition sessions in a male FH team competing in the first german division.